The data alchemists. - Savage, P.R.
XML, the Extensible Mark-up Language will, in the next few years, replace HTML, the code that defines how a document looks when viewed by a Web browser. XML provides structure as well as looks to a document. While HTML can format things like headlines and tables, XML can define things like dates, invoice numbers, and prices. This means you can build data files, Web pages, or documents that can be probed with simple questions - for example, "find all prices above a certain amount" - or more nuanced ones, such as "tell me which professors in this journal article database were funded by which corporations to research molecular beam epitaxy". Relying on semantics and logic instead of key words only speeds up any search you need to make. To make this kind of smart searching possible, one further concept comes into play: the resource description format (RDF), a way of specifying the relationship between entities.
Keywords: Extensible Mark-up Language; RDF; Web browser; XML; Entity relationship specification; Logic searching; Resource description format; Semantics; Smart searching